Curcumin modulates gut microbiota and improves renal function in rats with uric acid nephropathy - Xu, Xueling; Wang, Huifang; Guo, Dandan; Man, Xiaofei; Liu, Jun; Li, Junying; Luo, Congjuan; Zhang, Ming; Zhen, Li; Liu, Xuemei (Renal failure, 2021)
It is well known that the progression of hyperuricemia disease often contributes to renal dysfunction. However, there have been few studies on uric acid nephropathy (UAN), especially its relationship with gut microbiota. UAN is usually accompanied by disordered intestinal flora, and damaged gut barrier, which are closely related to tubulointerstitial fibrosis, and systemic inflammation. In previous studies, it has been confirmed that curcumin could alleviate tubulointerstitial fibrosis, and improve renal function through its antioxidant, anti-apoptotic, and anti-inflammatory efficacies. However, the effects curcumin exerts on intestinal flora in uric acid nephropathy are still unknown. Therefore, we used next-generation sequencing technology to investigate the effects of curcumin on gut microbiota in a rat model of UAN induced by adenine and potassium oxonate, and rats were randomly divided into control, model or curcumin treatment groups. The results demonstrated that, compared to the model group, the treatment group showed decreased serum uric acid (156.80 ± 11.90 μmol/L vs. 325.60 ± 18.65 μmol/L, p < 0.001), serum creatinine (66.20 ± 11.88 μmol/L vs. 182.20 ± 8.87 μmol/L, p < 0.001) and BUN level (13.33 ± 3.16 mmol/L vs. 36.04 ± 6.60 mmol/L, p < 0.001). The treatment group also displayed attenuated renal pathological lesions and metabolic endotoxemia (25.60 ± 5.90 ng/mL vs. 38.40 ± 4.98 ng/mL, p < 0.01), and improved tightly linked proteins expression. Besides, curcumin altered the gut microbiota structure in UAN rats. More specifically, curcumin treatment protected against the overgrowth of opportunistic pathogens in UAN, including Escherichia-Shigella and Bacteroides, and increased the relative abundance of bacteria producing short-chain fatty acids (SCFAs), such as Lactobacillus and Ruminococcaceae. These results suggest that curcumin could modulate gut microbiota, fortify the intestinal barrier, attenuate metabolic endotoxemia, and consequently protect the renal function in UAN rats.